Bibliometric Review of Spiritual Intelligence: Trends and Applications in Education and Personal Growth - Judijanto, Loso (Eastasouth Institute, 2025)
Spiritual intelligence (SI) has emerged as a significant area of research, spanning disciplines such as psychology, education, leadership, and organizational behavior. This study conducts a bibliometric analysis of SI research using data from Scopus and visualization tools such as VOSviewer to identify key trends, influential authors, and thematic developments. The findings reveal that SI is closely linked to psychological well-being, resilience, emotional intelligence, and ethical leadership, highlighting its interdisciplinary nature. Early research (2018–2019) primarily focused on mental health and personal development, whereas recent studies (2021–2022) have explored SI in leadership, organizational commitment, and artificial intelligence. The analysis also shows regional research hubs, with Iran, Malaysia, Indonesia, and Western countries playing central roles in SI studies. Despite its increasing academic recognition, SI research faces challenges in standardized measurement, integration into education and professional settings, and cross-cultural applicability. Future research should focus on developing reliable assessment tools, expanding SI’s role in leadership and AI ethics, and conducting comparative cultural studies. This study contributes to the growing body of SI literature by mapping its evolution, applications, and emerging research directions.